Arranjos de governança e participação no setor de turismo: analisando as experiências na Paraíba e no Rio Grande do Norte - Silva, Gutenbergue Viana da (2018)
This dissertation is part of the theme of governance and social, political and administrative participation in public management, focusing on the planning of the tourism sector, which has been discussed in Brazil for more than 50 years. Currently, the most important public policy oriented to this end is the Tourism Regionalization Program - Roteiros do Brasil (PRT), launched in 2004 in the first Lula government and reissued in 2013 in the first Dilma Rousseff government. This program also has as main goal to definitively integrate the country in the international tourist market. This policy determines at local / regional levels the constitution of Regional Governance Instances, characterized as institutional arrangements that must, necessarily, be guided by the participation of diverse segments of society. In this sense, the objectives of this research were to understand how these institutional arrangements are effected, what their peculiarities are, how they are characterized pragmatically and to what extent the social participation in public management and the governance associated with it was paradigmatic in the tourism sector. For this, a comparative work was chosen between two distinct experiences of implementation of this policy: the Tourist Board of the Seridó of Rio Grande do Norte and the Forum of Tourism of the Brejo in Paraíba. In order to achieve these objectives, a bibliographical review was carried out on the question of participation and, consequently, the governance linked to it in the public management of tourism. In this sense, studies and research were carried out by the research group of the Postgraduate Program in Tourism of the Federal University of Rio Grande do Norte entitled "Planning and Organization of Tourism - GEPPOT" and the Research Group "Development, Planning and Tourism "Linked to the undergraduate course in Tourism of the UFPB. These databases were inputs to understand the historical and current panorama of the regionalization policy, as well as to better understand how the governance arrangements in both states function and characterize each other, comparing them. In addition, a semi-structured profile interview was conducted with representatives of the two regions, which allowed updating information contained in the aforementioned works. From the results, it can be concluded that both experiences of governance arrangements have striking conflicts and contradictions in their forms of organization. The advice of the Polo Seridó is somewhat below the comparison with the Brejo Forum, because this space has effectively established itself around the participatory and regional assumptions of public policy and is characterized as a sui generis model of tourism governance, in which the private sector has plenty of strength and leadership. In contrast, the Polo Seridó council remains immersed in the same problems attributed to the lack of technical and institutional capacity of the public power.